2022
DOI: 10.3390/pharmaceutics14050980
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Inhibition of Breast Cancer Cells and Tumors in Mice by Carotenoid Extract and Nanoemulsion Prepared from Sweet Potato (Ipomoea batatas L.) Peel

Abstract: The objectives of this study were to determine carotenoid composition in sweet potato (TNG66) peel and prepare carotenoid nanoemulsion to study its inhibition effect on breast cancer cells MCF-7 and tumors in mice. Results showed that a total of 10 carotenoids were separated within 30 min by employing a YMC C30 column and a gradient mobile phase of methanol/acetonitrile/water (74:14:12, v/v/v) and dichloromethane (B) with a flow rate of 1 mL/min, column temperature of 25 °C, and detection wavelength of 450 nm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…For the preparation of nanoemulsions, highly unsaturated soybean oil was selected based on its abundance and low cost as well as its ability to protect bioactive compounds, as indicated by McClements and Jafari [ 32 ] and Hsu and Chen [ 33 ]. Moreover, various trial studies based on the calculation of HLB (hydrophilic–lipophilic balance) value were conducted to choose the appropriate surfactant/cosurfactant type and amount to stabilize the soybean oil containing xanthone or anthocyanin extract and obtain stable nanoemulsions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the preparation of nanoemulsions, highly unsaturated soybean oil was selected based on its abundance and low cost as well as its ability to protect bioactive compounds, as indicated by McClements and Jafari [ 32 ] and Hsu and Chen [ 33 ]. Moreover, various trial studies based on the calculation of HLB (hydrophilic–lipophilic balance) value were conducted to choose the appropriate surfactant/cosurfactant type and amount to stabilize the soybean oil containing xanthone or anthocyanin extract and obtain stable nanoemulsions.…”
Section: Resultsmentioning
confidence: 99%
“…For the proportion of G0/G1 phase, a significant decline ( p < 0.05) by 10.92, 11.41 and 13.58%, respectively, was found following treatment with the xanthone extract at 6, 8 and 10 μg/mL, as well as 17.17, 19.17 and 19.84% when treated with the xanthone nanoemulsion at the same doses. By comparison, xanthone nanoemulsion was more effective than xanthone extract in decreasing the proportion of the G0/G1 phase, probably caused by the enhanced permeation and retention (EPR) effect for easier penetration into cells [ 33 ]. Similar to the sub-G1 phase, a significant rise ( p < 0.05) in the S phase proportion by 1.48, 1.73 and 3.08%, respectively, was found for the xanthone extract at 6, 8 and 10 μg/mL, as well as 2.70, 3.11 and 3.21% for the xanthone nanoemulsion at the same doses, when compared to the control treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the combination of carotenoids at equimolar concentrations can inhibit the growth of cancer cells more effectively than individual carotenoids [ 32 ]. Another study also demonstrated that carotenoid extracts effectively inhibited the activity of MCF-7 human breast cancer cells and suppressed tumor growth in female BALB/c nude mice [ 46 ]. Russo M et al proposed that the carotenoid mixture exhibits a stronger inhibitory effect on MCF-7 cell proliferation, which may be attributed to its synergistic effect [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whey protein and soy lecithin showed better results in the context of a smaller droplet size (<150 nm) and interfacial tension, which ultimately contributed to the improved stability of the carotenoid NE [110]. In a recent study, carotenoid NE produced a prominent antiproliferative effect in breast cancer cells (MCF-7) and tumor-bearing mice by virtue of considerable reduction in epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF) levels compared to the carotenoid extract [111].…”
Section: β-Carotenoidmentioning
confidence: 99%